Megaco a new standard for media gateway control. - Taylor, T.
Arango and Huitema (1998) were the first to propose a new architecture for voice-over-IP networks, physically separating call control from media and bearer control. This separation created the need for a new class of protocol to link the two units. The Media Gateway Control Protocol is now seeing limited deployment for that purpose. However, MGCP is optimized for circuit to packet voice connections and has a North American bias in the types of events it can handle. A new protocol has been standardized by the IETF Megaco Working Group working together with ITU-T Study Group 16, which has been published as both a standards-track RFC and ITU-T Recommendation H.248. This protocol extends media gateway control to include a transport-independent connection model, support for more advanced services such as multimedia conferencing, and support for operation in countries around the world. The present article provides a technical description of the features of Megaco/H.248
Keywords: IETF Megaco Working Group; ITU-T Study Group 16.; Media Gateway Control Protocol; Megaco/H.248.; North American bias; Advanced services; Architecture; Bearer control; Call control; Circuit to packet voice connections; Media control; Media gateway control; Multimedia conferencing; Optimization; Protocol; Standard; Technical description; Transport-independent connection model; Voice-over-IP networks